Endodontic Treatment in Patients Under Radiotherapy Treatment: Literature Review (Research, Society and Development, 2021)
The prevalence of head and neck cancer has been increasing more and more and is associated with pain, disfigurement, dysfunction, psychosocial suffering and death. Among the forms of treatment there are radiotherapy, chemotherapy, surgery, as well as their combination. One of the biggest complications of radiotherapy is osteoradionecrosis. It presents xerostomia, and consequently radiation caries, which appear due to a change in the oral microbiota, creating a more acidic environment. These microorganisms cause an inflammation inside the tooth that later develops into pulp necrosis. With this, the objective of this work is to carry out a review in the literature that shows how to perform an atraumatic endodontic treatment, highlighting the conduct for endodontic treatment in cancer patients and how to avoid osteoradionecrosis of the jaws. Search strategies were used in five databases: PubMed; Cochrane; LILACS; Web of Science; and Scopus, with the keywords: "head neck cancer", "root canal therapy", "endodontic treatment". The main reason for performing endodontic treatment is the fact that a more conservative treatment can be performed, being an alternative to avoid tooth extraction and reduce the possibility of causing osteonecrosis. In patients who are in the pre-radiotherapy treatment phase, the protocol suggests a normal treatment. In the phases during and after irradiation treatment, the cleaning of the channels must be non-traumatic. If a tooth has sufficient structure, compatible with a good prognosis for rehabilitation, but with an inflammatory lesion or irreversible pulp inflammation, endodontic treatment is ideal.